A randomised open label parallel group study on evaluation of efficacy and safety of gemifloxacin versus cefpodoxime in chronic obstructive pulmonary disease patients. - RENUKA. A,; VASANTHI. C,; DARLING CHELLATHAI, (International Journal of Pharma and Bio Sciences, 2017)
One of the most important cause of death is Chronic Obstructive Pulmonary Disease.1 The present study is a randomised, open label, parallel group study, distinguishing the safety, efficacy of Cefpodoxime vs Gemifloxacin in Chronic Obstructive Pulmonary Disease patients. The primary objective of the study is to compare the efficacy of Gemifloxacin versus Cefpodoxime in the management of Chronic Obstructive Pulmonary Disease. The secondary objective of the study is to explore the safety of the two drugs. The study was conducted at the OP block of the Chest Medicine Department of Sri Ramachandra Medical College and Research Institute.100 patients participated in the study, 50 patients in each group. Tab. Cefpodoxime 200 mg bd for 7 days was given to 50 subjects and Tab. Gemifloxacin 320 mg once daily for 5 days was given to 50 subjects. In the Gemifloxacin group, the mean FEV1 was 64.944% before treatment and 73.790% post medication. The transformation in FEV1 was 13.62%, Standard deviation was 1.3600. In the Cefpodoxime group, the mean FEV1 was 64.102% before treatment and 69.574% after treatment. The change in FEV1 was 8.54%, Standard deviation was 1.3898. The difference between the treatment groups was statistically significant and p value = 0.005. The present study has exposed that Gemifloxacin is more efficacious than the widely used antibiotic, Cefpodoxime in Chronic Obstructive Pulmonary Disease patients.